Design of Smart Home Security System With Face Recognition And Voice Command Based On Internet of Things - Ketty Siti Salamah; Lutfi Arif Setiyawan; Imelda Uli Vistalina Simanjuntak (ELKHA : Jurnal Teknik Elektro, 2023)
All individuals really need technology to accelerate development or enhance the development of both individuals and groups. A smart door lock is a feature embedded in a smart home to make everyday life easier. Given the importance of security for valuables stored in the house and the fact that security is required in accessing the house, the research was conducted with the goal of helping meet the needs of an easy-to-implement home security system. By utilizing the Raspberry Pi minicomputer as a processor, the webcam as a face detector, and Voice Command for detecting voice codes, which will then be processed by the Raspberry Pi using OpenCV to determine whether a human face is there or not, calculating the distance between facial features such as eyes, nose, and mouth as well as the code, the given vote is either true or false. After the face is recognized and the sound code is correct, the Raspberry Pi will issue an order to the servo to open the solenoid so that the home door can be accessed by the home owner, and there will be a message sent via telegram if someone tries to access this system. Based on the system tests that have been carried out, it turns out that the facial recognition system has an accuracy of 75%, a positive error of 25%, and a negative error of 0%, so it can be concluded that this system is safe enough to be applied in a home door security system.